أثر عوائق الدخول على أداء مؤسسة موبيليس لصناعة خدمة الهاتف النقال في الجزائر - سايحي, الخامسة; هاني, نوال; بن صغير, فاطمة الزهرة (جامعة الوادي University of Eloued, 2020)
تهدف هذه الدراسة إلى التعرف على طبيعة عوائق الدخول في صناعة خدمة الهاتف النقال في الجزائر، وذلك لما تلعبه هذه العوائق من تأثير مباشر على أداء مؤسسة موبيليس والتي تعتبر من أهم المؤسسات في قطاعها، وهي أول متعامل في هذا القطاع، بحيث تناولت الدراسة الإطار النظري لعوائق الدخول ثم التطرق إلى أداء المؤسسات بشكل عام، ليتم فيما بعد محاولة إسقاط الدراسة النظرية على واقع أداء مؤسسة موبيليس لتقييمه في ظل البيئة التنافسية لمعرفة طبيعة ما يواجهها من فرص وتهديدات لكي تحافظ على البقاء والاستمرار. من بين النتائج المتوصل إليها أن صناعة خدمة الهاتف النقال تخضع لعوائق دخول طبيعية، وعوائق استراتيجية، وعوائق حكومية أثرت ايجابا على أداء المؤسسة محل الدراسة موبيليس. This study aims to identify the nature of barriers to entry in the mobile service industry in Algeria, This is due to the direct impact of these obstacles on the performance of the Mobilis Foundation, which is considered one of the most important institutions in its sector, She is the first customer in this sector, as the study examined the theoretical framework for entry barriers and then touched on the performance of institutions in general, After that, an attempt is made to drop the theoretical study on the reality of the performance of the Mobilis Foundation, to evaluate it in the competitive environment, to know the nature of the opportunities and threats it faces in order to maintain survival and continuity. Among the findings are that the mobile service industry is subject to natural entry barriers, and strategic barriers, and government barriers that have positively affected the performance of the institution under study Mobilis.
The impact of entry barriers on the performance of the Mobilis Foundation for the mobile service industry in Algeria
مقال
Keywords: عوائق الدخول، أداء المؤسسة، عوائق الدخول في صناعة خدمة الهاتف النقال في الجزائر، أداء مؤسسة موبيليس.